The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1017/s1368980011002369
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of anaemia and iron deficiency in HIV-infected pregnant women in Tanzania: a potential role for vitamin D and parasitic infections

Abstract: Objective Anaemia is common during pregnancy, and prenatal Fe supplementation is the standard of care. However, the persistence of anaemia despite Fe supplementation, particularly in HIV infection, suggests that its aetiology may be more complex and warrants further investigation. The present study was conducted to examine predictors of incident haematological outcomes in HIV-infected pregnant women in Tanzania. Design Prospective cohort study. Cox proportional hazards and binomial regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 45 publications
(63 reference statements)
7
39
3
1
Order By: Relevance
“…12,13 In a study in Tanzania, low CD4 T-cell count, high erythrocyte sedimentation rate, and vitamin D insufficiency were noted as main predictors of anemia in HIV-infected pregnant and postpartum women. 14 Patients who were being treated for TB were at higher risk for anemia. Previous studies have shown that anemia, along with other factors such as HIV disease progression and CD4 ALT = alanine aminotransferase; ART = antiretroviral treatment; AZT = zidovudine; BMI = body mass index; CI = confidence interval; D4T = stavudine; EFV = efavirenz; TDF = tenofovir; FTC = emtricitabine; Hgb = hemoglobin; HIV = human immunodeficiency virus; IDA = iron deficiency anemia; MCV = mean corpuscular volume; NVP = nevirapine; TB = tuberculosis; 3TC = lamivudine; WHO = World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In a study in Tanzania, low CD4 T-cell count, high erythrocyte sedimentation rate, and vitamin D insufficiency were noted as main predictors of anemia in HIV-infected pregnant and postpartum women. 14 Patients who were being treated for TB were at higher risk for anemia. Previous studies have shown that anemia, along with other factors such as HIV disease progression and CD4 ALT = alanine aminotransferase; ART = antiretroviral treatment; AZT = zidovudine; BMI = body mass index; CI = confidence interval; D4T = stavudine; EFV = efavirenz; TDF = tenofovir; FTC = emtricitabine; Hgb = hemoglobin; HIV = human immunodeficiency virus; IDA = iron deficiency anemia; MCV = mean corpuscular volume; NVP = nevirapine; TB = tuberculosis; 3TC = lamivudine; WHO = World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin was categorized as 11 g/dL (normal), 8.5 and 11 g/dL (anemic), and 8.5 g/dL (severely anemic). [16][17][18] In bivariate analyses, we compared the distribution of the continuous SOFA score outcome between categories of each predictor using the Kruskall Wallis test. Adjusted mean differences and 95% confidence intervals (CIs) for the continuous SOFA score outcome were estimated from multivariable linear regression using empirical variances.…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported that 'micronutrient supplementation and infectious disease control, is warranted in HIV-infected women in resource-limited settings' (1) . I agree completely with this useful suggestion.…”
Section: Madammentioning
confidence: 99%
“…In addition to Hb concentrations, serum ferritin and transferrin receptor, and at least one acute-phase protein, such as C-reactive protein or a-1 acid glycoprotein, would further improve Fe assessment in the context of inflammation and infection. With an average of nine Hb measurements per person (over 9000) collected prospectively at the time of the study, it was not possible to conduct a more detailed analysis of Fe status on all samples collected prospectively in the ancillary analysis (1) . However, we previously published a detailed analysis of Fe status in the same cohort to examine the proportion of anaemia attributable to Fe deficiency among 584 HIV-infected women, including Hb, serum ferritin, serum transferrin receptor and C-reactive protein concentrations (7) .…”
Section: Madammentioning
confidence: 99%